Light Video Game Play is Associated with Enhanced Visual Processing of Rapid Serial Visual Presentation Targets. (February 2017) - Howard, Christina J.; Wilding, Robert; Guest, Duncan
There is mixed evidence that video game players (VGPs) may demonstrate better performance in perceptual and attentional tasks than non-VGPs (NVGPs). The rapid serial visual presentation task is one such case, where observers respond to two successive targets embedded within a stream of serially presented items. We tested light VGPs (LVGPs) and NVGPs on this task. LVGPs were better at correct identification of second targets whether they were also attempting to respond to the first target. This performance benefit seen for LVGPs suggests enhanced visual processing for briefly presented stimuli even with only very moderate game play. Observers were less accurate at discriminating the orientation of a second target within the stream if it occurred shortly after presentation of the first target, that is to say, they were subject to the attentional blink (AB). We find no evidence for any reduction in AB in LVGPs compared with NVGPs.